A Review on Progressive Collapse and Its Types (Journal of Civil Engineering Researchers, 2024)
The occurrence of progressive structural damage during seismic events and nearby explosions presents a significant challenge. Progressive failure refers to the situation in which a localized failure in a structural element triggers the failure of neighboring elements, leading to further collapses within the building. There are limited instances of structures experiencing either partial or complete progressive failure. Notably, such occurrences were observed following the partial collapse of the renowned Ronan Point1 residential building in London in 1968 and the destruction of the World Trade Center buildings on September 11, 2001. The engineering community and various standardization committees have focused their attention on this significant issue and have initiated the implementation of enhanced design methods to mitigate progressive failure.
Keywords: progressive collapse; progressive failure; Structural damage; Column failure; Load redistribution